Mustaqillat: navigating women's mobilities in post-2011 Egypt - Eldamaty, Ghadeer Ahmed (AUC Knowledge Fountain, 2020)
Following the Egyptian revolution of January, the 25th, 2011, the term women's independence, istiqlal ijtma'ay, has been widely used by young Egyptian women. A mustaqilla (independent woman) identifies herself as a woman who is socio-economically independent from her family, lives on her own, and works to support herself. This thesis is concerned with the emergence of independent women, mustaqillat, as a social phenomenon, and questions how the phenomenon of istiqlal is constructed. What are its socio-economic dimensions, and associated meanings? Based on an ethnographic fieldwork with a group of Egyptian women who identify themselves as mustaqillat, this thesis focuses on mustaqillat who moved from their governorates to Cairo, and other cities in Egypt, for the purpose of having a greater mobility.